2019
DOI: 10.1002/jcp.28554
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic stem cells differentiated into neuron‐like cells using SB431542 small molecule on nanofibrous PLA/CS/Wax scaffold

Abstract: Electrospun nanofibrous scaffolds show huge potential to improve the neurological outcome in central nervous system disorders. In this study, we cultured mouse embryonic stem cells (mESCs) on an electrospun nanofibrous polylactic acid/ Chitosan/Wax (PLA/CS/Wax) scaffold and surveyed the attachment, behavior, and differentiation of mESCs into neural cells. Differentiation in neural-like cells (NLCs) was investigated with a medium containing SB431542 as a small molecule and conjugated linolenic acid after 20 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Generally, mammalian cells have a high demand of a proper support surface. Thus, some material such as gelatin, collagen matrix and matrigel (BD, USA) were used as support surface for culture of pluripotent stem cells like embryonic stem cells or induced pluripotent stem cells[49-52]. The BM of hAM was mainly consisted of collagen and proven to be a good supporting scaffold [12,53].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, mammalian cells have a high demand of a proper support surface. Thus, some material such as gelatin, collagen matrix and matrigel (BD, USA) were used as support surface for culture of pluripotent stem cells like embryonic stem cells or induced pluripotent stem cells[49-52]. The BM of hAM was mainly consisted of collagen and proven to be a good supporting scaffold [12,53].…”
Section: Discussionmentioning
confidence: 99%
“…67 The hydrophilic nature of PLA-CS fibers was found to have increased, thereby promoting the proliferation and osteogenic differentiation of marrow mesenchymal stem cells on the fibers. 69,70 The combination of PLGA with multiwalled CNTs and BC was found to enhance osteogenic differentiation and facilitate regeneration. 71 The study revealed that incorporating soluble eggshell membrane protein led to enhanced spinnability and mechanical strength of PLGA.…”
Section: Materials Of Electrospun Nanofiber Scaffoldsmentioning
confidence: 99%
“…Materials made from synthetic polymers exhibit high spinnability and favorable mechanical properties. , Nevertheless, they are unable to enhance cell adhesion, proliferation, and differentiation, whereas natural polymers typically exhibit superior bioactivities despite having inferior mechanical strength. , Researchers have shown a tendency to combine synthetic and natural polymers using cospinning, coaxial electrospinning, and surface coating modification. , CS, GEL, and COL are incorporated to markedly decrease the hydrophobic nature of nanofibers and enhance cell adhesion . The hydrophilic nature of PLA-CS fibers was found to have increased, thereby promoting the proliferation and osteogenic differentiation of marrow mesenchymal stem cells on the fibers. , The combination of PLGA with multiwalled CNTs and BC was found to enhance osteogenic differentiation and facilitate regeneration . The study revealed that incorporating soluble eggshell membrane protein led to enhanced spinnability and mechanical strength of PLGA …”
Section: Materials Of Electrospun Nanofiber Scaffoldsmentioning
confidence: 99%
“…At the cellular level, neural stem cells cultured on well‐arranged PLA fibers showed improved protuberances growth. [ 224 ] Similarly, SCs cultured on aligned PCL fibers, were observed to have their cell cytoskeleton and nuclei aligned and elongated along the fiber axes and, in addition, have the propensity of promoting SCs maturation. [ 225,226 ] As an explanation for the above phenomenon, differential gene expression of neurotrophic factors were observed in aligned, random, and smooth films.…”
Section: Morphology Cue‐based Strategies For Pnrmentioning
confidence: 99%